Characterization of phytoplankton size-structure based productivity, pigment complexes (HPLC/CHEMTAX) and species composition in the Cochin estuary (southwest coast of India): special emphasis on diatoms - Meenu Paul; Madhu Nikathithara Velappan; Ullas Nanappan; Vineetha Gopinath; Rehitha Thekkendavida Velloth; Ashwini Rajendran; Maheswari Nair; Anil Peariya (Oceanologia)
Seasonal studies on size-fractionated phytoplankton productivity (biomass and primary production), marker pigments, and species composition and abundance were carried out in the Cochin estuary (CE), located on the southwest coast of India, to identify the critical environmental factors that control the consistent preponderance of diatoms. The overall results of the study showed a significant contribution of small-sized phytoplankton, specifically nanophytoplankton (2–20 µm), to the total chlorophyll a and primary production in the estuary, regardless of seasons. Diatoms constituted the major phytoplankton taxa, showed an exceptional seasonal scale increase in numerical abundance during the post-southwest monsoon. The relative increase in fucoxanthin (biomarker of diatoms) over other marker pigments substantiated the numerical dominance of diatoms throughout the sampling periods. This is the first study in the CE in which phytoplankton marker pigments have been detected and elucidated the seasonality of functional groups based on HPLC/chemotaxonomy analytical approaches. The prevalence of high DiatDP and diatom chlorophyll a equivalent (estimated by CHEMTAX), further confirmed the preponderance of diatoms in the CE, despite the intermittent dominance of cyanophytes and cryptophytes (monsoon period). The consistent increase in SPM levels (> 25 mg L–1), established at all sampling stations, indicated that the water column turbidity might be one of the significant environmental factors hindering the growth of large-sized phytoplankton (ca. >20 µm) in the CE even if the system invariably holds high inorganic nutrients, irrespective of seasons.